Cytotoxic necrotizing factor 1 from Escherichia coli: a toxin with a new intracellular activity for eukaryotic cells - Boquet, P (Folia microbiologica, 1998)
Certain pathogenic Escherichia coli strains elaborate a toxin, the cytotoxic necrotizing factor type 1 (CNF1). CNF1 covalently and specifically modifies the p21 Rho GTP-binding protein in mammalian cells by deamidation of the p21 Rho glutamine 63. CNF1 modification of Rho leads to permanent activation of the GTP-binding protein by blocking intrinsic and RhoGAP GTPase activities. Rho activation by CNF1 induces reorganization of the actin cytoskeleton into large stress fibers and the multiplication of focal contact points. Deamidation is a new catalytic activity described for an intracellularly acting toxin.
Keywords: bakteriální toxiny; Bacterial Toxins; eukaryotické buňky; Cytoskeleton; proteiny vázající GTP; lidé; GTP-Binding Proteins; Cytotoxins; cytotoxiny; rho GTP-Binding Proteins; Escherichia coli; Eukaryotic Cells; Escherichia coli Proteins; proteiny z Escherichia coli; cytoskelet; Rho proteiny vázající GTP; Humans